Peningkatan Kreativitas Siswa melalui Project Based Learning dalam Pembelajaran IPS di SMPN 3 Kedungwaru - Andromeda Putri Herastita Anggipitasari; Larasati Widoningtyas (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the implementation of the Project Based Learning (PjBL) model in enhancing students' creativity in Social Studies (IPS) learning for Grade VIII at SMP Negeri 3 Kedungwaru. The research method used is a qualitative approach with a case study design. Data collection techniques include observation, interviews, and documentation. The results show that the implementation of PjBL can enhance students' creativity through project activities that encourage critical thinking, collaboration, and problem-solving. Students become more active, confident in expressing ideas, and capable of producing innovative work. Despite several challenges such as limited time and varied student participation, PjBL has proven to be effective in creating contextual and meaningful learning.